Factors that Influence Teacher Self-Efficacy in Providing Education in the School Environment - Wijayanto, Pikir Wisnu; Supriyadi, Tugimin; Satyaninrum, Ika Rahayu; Judijanto, Loso; Sanulita, Henny; Lumbantoruan, Jitu Halomoan (Universitas Pendidikan Indonesia, 2024)
Teacher self-efficacy is considered important and a priority in the learning process. Teachers who do not have self-efficacy have a negative impact and are related to ability. This is an urgent matter to research to find out the influencing factors of ability and self-efficacy in carrying out education in the school environment. The method used is quantitative. Subjects numbered 263 from a population of 30 schools. Data collection techniques using questionnaires. The instruments in the questionnaire are rated on a Likert scale of points 1 to 5 points. Data analysis techniques using Statistics version 25.0 and determining the mean, percentage, and standard deviation as well as inferential analysis are used for regression and correlation. The results and findings show that the level of teacher self-efficacy in implementing education is in the medium category. It was also found that teachers' perceptions of the implementation of leadership were moderate and environmental awareness was also moderate. However, the teacher's attitude in the environment is positive and good. In conclusion, teacher self-efficacy in implementing education must coincide with teacher awareness, teacher perception of leadership, and practice of loving the environment. Recommendations need to further examine teacher self-efficacy in the process towards students in the classroom. This research contributes to providing information about Teacher Self-Efficacy which influences the learning process in schools.